FORTA(Fit-fOR-The-Aged)-based medication optimization: retrospective analysis of experiences from an unconventional outpatient service - Rieg, Sophia; Wehling, Martin (European geriatric medicine, 2020)
To map prescription considerations concerning older community dwelling subjects emerging in a special gerontopharmacology hospital-based consultation.